Evaluation of Antioxidant and Antidiabetic Potential of Crude Protein Extract of Pumpkin Seeds (Cucurbita maxima L.) - Monica, Sarah Jane; John, Sheila; K, Saraswathi; R, Madhanagopal; P, Arumugam (Asian Journal of Biological and Life Sciences, 2020)
Pumpkin seeds are a rich source of protein and fibre. Proteins present in pumpkin seeds have received less attention in spite of their significant biological activities. The objective of the present study was to evaluate the antioxidant and antidiabetic activity of crude protein obtained from pumpkin seeds. Protein was extracted using pre-chilled phosphate buffer extraction (0.2M; pH- 7), followed by acetone precipitation and dialysis. The protein content of pumpkin seeds was estimated using Bradford’s method. The electrophoretic profile was determined using SDS PAGE. Antioxidant activity was determined using DPPH●radical, ABTS●+radical cation, Fe3+reduction and phosphomolybdenum reduction assay. Antidiabetic activity was determined using alpha amylase inhibition assay. Mean values of different concentrations were tested for significance using one way Anova followed by Tukey’s test. The protein content of pumpkin seed was 100.48 ± 0.72 mg/ mL and the molecular weight of the extracted proteins ranged from 25 to 45 kDa. The proteins present in pumpkin seeds showed significant antioxidant activities in a dose dependent manner (p<0.05). The IC50value of DPPH●radical and ABTS●+radical scavenging assay was 670 μg/mL and 3.49μg/mL. Pumpkin seed proteins showed significant alpha-amylase inhibitory activity (p<0.05) and the IC50value was 127.94 μg/mL. The results of the present study indicate the biological health promoting effects of plant proteins and their use as a functional food component.
Keywords: Antidiabetic activity; Antioxidant potential; Plant protein; Pumpkin seeds; SDS-PAGE